Analisys of Effect of Outside Air Speed To Air Humidity and Refrigerator Coefficient of Performance - Riman Sipahutar; Ferry Irawan (Universitas Sriwijaya, 2016)
Air conditioning is essential for most humans and are associated with human thermal comfort. At conditioned room where the condition can occur outside air (atmosphere) into the room. Althouht the author was interested in researching this influx of outside air. The aims of this research would be able to examine the effect of the entry of outside air to the room air humidity and refrigerator coefficient of performance. The method used is to perform laboratory-scale experiment with conditioned room with air conditioning or no air conditioning which then incorporate outside air into the room. From this experiment would get experimental result, the result of theoretical calculation, and the result of calculation by using the simulator program. By entering the outside air was obtained that the outside air increases the humidity in the room and affect refrigerator coefficient of performance. The experimental results showed that the average maximum condition occurs at a speed of 1 m/s and at 20 minutes. It can be concluded that the outside air entering the room using the air conditioner would improve indoor air humidity and increase the cooling load means affect refrigerator coefficient of performance. And in a room without air conditioner caused indoor air humidity getting closer to the comfort zone.